2021
DOI: 10.1016/j.whi.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Birth Outcomes Among Women of Advanced Maternal Age With and Without Health Conditions in Maryland

Abstract: Background: Advanced maternal age (AMA) has been linked to both higher risk of adverse birth outcomes and higher levels of comorbidities. It is unclear if adverse outcomes are higher for older healthy women. This study examined the association between AMA and adverse birth outcomes among women with and without preexisting and pregnancyrelated health conditions. Methods: Analysis of data for 14,933 singleton births between 2004 and 2015 from the population-based Maryland Pregnancy Risk Assessment Monitoring Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…This study reaffirms maternal age and race disparities in low birth weight demonstrated in the literature [ 26 ]. Racial disparities are typically explored without taking age groups into account, despite age being an important biologic factor for several outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…This study reaffirms maternal age and race disparities in low birth weight demonstrated in the literature [ 26 ]. Racial disparities are typically explored without taking age groups into account, despite age being an important biologic factor for several outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…Although ENM is a composite outcome of multiple clinical factors, we were not able to directly capture factors driving the patterns observed in this cohort as it was based on national database with limited information. However, maternal age-related factors that are known to be associated with perinatal death, such as congenital birth defect 14 , preterm birth 18 , and preeclampsia 26 , and these factors are likely to be more severe in each category for > 40 years 7,17 . Thus, it can be carefully speculated that the reason ENM remained still high in the mothers over 40 years of age despite the degree of social support, may be accountable to congenital anomalies, chromosomal abnormality and extremely preterm or very low birth weight complicating neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal characteristics, such as older age 13,14 and obesity 15 , have been linked with various adverse pregnancy outcomes, including complications during pregnancy and delivery leading to increased morbidity in the newborn. In our study, maternal age and maternal parity did not differ, and maternal weight prior to conception and weight gain during pregnancy were similar for mothers of infants with CH as for those in the general population.…”
Section: Discussionmentioning
confidence: 99%